2019
DOI: 10.1177/0142723719887313
|View full text |Cite
|
Sign up to set email alerts
|

Parental reports of communicative development at the age of 36 months: The Estonian CDI-III

Abstract: Parental reports are a widely-used source of information about infants’ and toddlers’ communicative skills, but parent-report instruments valid for children older than 30 months are less known. This study explored individual variability in children’s communicative skills at the age of 3;0 via parental reports using the Estonian (E) CDI-III. The validity of ECDI-III was established through correlations with another parent-report instrument (ECDI-II) and a standardized examiner-administered language assessment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 46 publications
10
42
0
Order By: Relevance
“…A large correlation between the vocabulary and syntax scores of the CDI-III-PT was found, similarly to the ones obtained in other CDI-III versions (Eriksson, 2017;Tulviste and Schults, 2020). When correlations between the syntax scale and each of the different sections of the vocabulary scale are considered, higher correlation is found between the syntax scale and the section Vocabulary-mental terms.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…A large correlation between the vocabulary and syntax scores of the CDI-III-PT was found, similarly to the ones obtained in other CDI-III versions (Eriksson, 2017;Tulviste and Schults, 2020). When correlations between the syntax scale and each of the different sections of the vocabulary scale are considered, higher correlation is found between the syntax scale and the section Vocabulary-mental terms.…”
Section: Discussionsupporting
confidence: 80%
“…Regarding validity evidence, mediumto-large intercorrelations between the subscales of the CDI-III and medium correlations between the scores in the CDI-III and other standardized measures were found. The results of the study also indicated that being a girl, having a higher number of older siblings, having attended day care for a longer time, having a mother with higher educational levels, and having no reported language difficulties are factors associated with a higher score in the vocabulary subscale (Tulviste and Schults, 2020). The effect of these demographic variables on the remaining CDI-III subscales was not tested.…”
Section: Previous Adaptations Of the Macarthur-bates Communicative Development Inventories (And The Particular Case Of The Cdi-iii)mentioning
confidence: 87%
See 3 more Smart Citations